Effect of Empagliflozin on Thioacetamide-Induced Liver Injury in Rats: Role of AMPK/SIRT-1/HIF-1α Pathway in Halting Liver Fibrosis - Marwan A. ElBaset; Rana S. Salem; Fairouz Ayman; Nadeen Ayman; Nooran Shaban; Sherif M. Afifi; Tuba Esatbeyoglu; Mahmoud Abdelaziz; Zahraa S. Elalfy (MDPI AG, 2022)
Hepatic fibrosis causes severe morbidity and death. No viable treatment can repair fibrosis and protect the liver until now. We intended to discover the empagliflozin's (EMPA) hepatoprotective efficacy in thioacetamide (TAA)-induced hepatotoxicity by targeting AMPK/SIRT-1 activity and reducing HIF-1α. Rats were treated orally with EMPA (3 or 6 mg/kg) with TAA (100 mg/kg, IP) thrice weekly for 6 weeks. EMPA in both doses retracted the serum GGT, ALT, AST, ammonia, triglycerides, total cholesterol, and increased serum albumin. At the same time, EMPA (3 or 6 mg/kg) replenished the hepatic content of GSH, ATP, AMP, AMPK, or SIRT-1 and mitigated the hepatic content of MDA, TNF-α, IL-6, NF-κB, or HIF-1α in a dose-dependent manner. Likewise, hepatic photomicrograph stained with hematoxylin and eosin or Masson trichrome stain of EMPA (3 or 6 mg/kg) revealed marked regression of the hepatotoxic effect of TAA with minimal injury. Similarly, in rats given EMPA (3 or 6 mg/kg), the immunohistochemically of hepatic photomicrograph revealed minimal stain of either α-SMA or caspase-3 compared to the TAA group. Therefore, we concluded that EMPA possessed an antifibrotic effect by targeting AMPK/SIRT-1 activity and inhibiting HIF-1α. The present study provided new insight into a novel treatment of liver fibrosis.